(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Corporate Social Responsibility has become imperative to any company’s strategic making decisions. Corporate have realized that government of any state or any countries will neither be able to get success in its endeavor to uplift the society nor alone can solve their key issues and environmental issues as well. With rapidly changing corporate environment many organization have setup separate CSR wings. This article has three aims. The First Aim is to deliver a massage, not only to big corporate or business house but also to small and medium organization even to capable citizens also.With the new companies Act 2013 in India (w.e.f. April 1st 2014), there is a legislative provision for making CSR mandatory for those companies having net worth of Rs. 500 Cr. or more or a turnover of Rs. 1000 Cr. or more or a net profit of Rs. 5 Cr. or more have to spend at least 2 of last three years average net profit on CSR activities as specified in schedule VII of this Act. India became the first country in the world to take this pioneer move.After enactment of this law, my Second Aim is to focus on how today CSR initiative is being used as tools of strategy by mainstream companies in order to achieve sustainable growth.And my Third Aim is to throw light on how some companies misuse these statutory CSR norms inappropriately.